KARAKTERISTIK KEPEMIMPINAN PRABU HAYAM WURUK DALAM KITAB NAGARAKRETAGAMA DITINJAU DARI TEORI KURT LEWIN DAN KEPEMIMPINAN JAWA DALAM ENDRASWARA - parjono M.Pd.B. (STABN Sriwjaya, 2023)
The background of this research is that the Wilwatikta kingdom (better known as Majapahit) reached its peak of glory during the leadership of Sri Rajasanagara (or better known as Prabu Hayam Wuruk) accompanied by Mahapatih Gajah Mada. The purpose of this study is to identify and recognize the leadership character of Prabu Hayam Wuruk which is written in the Nagarakretagama book.The method used in this research is library research. The approach method in this research uses the method of text analysis and text interrogation or often called hermeneutics which contains elements of expressing, explaining and translating. The object in this study as well as the primary data source is the Nagarakretagama book. Secondary and tertiary sources are obtained from studies of the Thematic Sutta Pitaka, books, journals, and writings that are relevant to the research theme. Data collection techniques in this study are collecting literature, classifying books, documents and other data, citing data, crosschecking, and grouping data. Techniques for validating data by extending time, persistence of observation and depth of reading, triangulation by utilizing sources outside the data. The data analysis technique is described by content analysis. The research was conducted at the Sriwijaya STABN library, the National Library and the Yogyakarta Regional Library (Grhatama Pustaka). The time of the research was carried out from July to December 2021.The results of the research and discussion in this study can be concluded: 1) Prabu Hayam Wuruk leadership characteristics: tolerance, integrity, democracy, wisdom, generosity, morality, and responsibility; 2) the leadership character of Prabu Hayam Wuruk based on Kurt Lewin's theory is included in the category of democratic (Democratic Leadership Style), namely a leader who involves followers in decision making; 3) The leadership character of Prabu Hayam Wuruk based on the level of Javanese leadership style in Endraswara is included in the Main (Main) level category where the virtues of Javanese leaders will always be liked by the people.